Analysis of cervical mucosal epithelium proliferation during the postmenopausal period - Shcheglov, Bogdan О.; Reva, Ivan V.; Puga, Dmitry P.; Koval, Irina P.; Shcheglova, Svetlana N.; Khamoshina, Marina B.; Usov, Viktor V.; Stegniy, Kirill V.; Reva, Galina V. (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. This study explores the proliferative growth of cervical mucosal epithelial cells during the postmeno pausal period, offering new insights on age-related changes in cervical tissues, a topic previously under-examined in post menopausal health research. By employing histologic analysis, immunostaining techniques, and Ki-67 mitotic index assess ment, this research provides novel data on the alterations in cervical epithelial cells during and after menopause. The findings enhance our understanding of the biological processes affecting cervical health in the postmenopausal phase, which is increas ingly significant as the global population ages and emphasizes the need for tailored healthcare approaches. The primary goal was to investigate the proliferative growth of cervical mucosal epithelial cells in postmenopausal women by assessment of Ki 67 gene activity in progesterone-positive cells in normal and pathological postmenopausal periods (PMPs) in the presence or absence of autonomic symptoms, manifested by mood instability, headaches and dizziness. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. This research involved analyzing tissue samples from 149 postmenopausal women with suspicion of malignancy using histologic and immunostaining methods to evaluate epithelial cell proliferation markers, with the Ki-67 mi totic index as a key measure. The average activity of the Ki-67 gene was evaluated using the global scoring method, with Ki-67 percentages below 2.5% considered low. Statistical analysis included both parametric and non-parametric methods, specifi cally Student’s t and Wilcoxon’s tests. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The study found a reduction in the proliferative activity of cervical mucosal epithelial cells during the normal post menopausal period, indicated by a significant decrease in Ki-67 expression in the exocervical zone and during the first year in the transformation zone and the endocervix (p<0.01). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Understanding the proliferative growth of cervical mucosal epithelial cells during the postmenopausal period helps to understand the dynamics of age-related cervical tissue. These results can lead to better prevention and monitoring strategies for cervical health in postmenopausal women.